New data on Asianopis (Aranei: Deinopidae) in Southeast Asia - Omelko, Mikhail M.; Fomichev, Alexander A. (Zootaxa, 2025)
Three new species, Asianopis lini sp. nov. (♂), A. naumenkoi sp. nov. (♀), and A. apo sp. nov. (♀) are described from Malaysia (Borneo), and Philippines (Luzon, Mindanao). Asianopis liukuensis (Yin, Griswold & Yan, 2002) is reported from Borneo for the first time and its male redescribed. The record of the A. liukuensis is the easternmost for its whole range. A new species group, the Asianopis apo-group, is proposed. Detailed descriptions, digital photographs and a distributional map are provided.